Implementation of Bhabinkamtibmas Counseling to prevent Criminal Acts against Children - Tiara Nur Raudah (Indonesian Journal of Police Studies, 2020)
Children are the seeds of the next generation of Indonesians, but children are often becoming the target of violence, law no.35 of 2014 amandment to law no. 23 of 2002 concerning Child Protection is a law created to ensure children can live, grow, develop and can participate optimally, without discrimination and violence. This study examines the Implementation of Bhabinkamtibmas Counseling to prevent crimes against children in the Garut police jurisdiction by using a qualitative approach, using field research methods, as well as data collection techniques by interviewing, observing, and reviewing documents. To discuss the problem the author uses theories and concepts contained in the National Police Regulation no. 3 of 2015 concerning Community Policing, as well as supporting theories of crime prevention, management theory, and communication theory. The results showed that there was still lack of people reporting the occurrence of crimes against children to the police, the need to improve not only quality but also the quantity of human resource both from their knowledge and skills. Improvement of Bhabinkamtibmas facilities and infrastructure along with the budget in the implementation of Bhabinkamtibmas activities, as well as increasing the intensity of outreach to the community so that it can further prevent criminal acts against children.